The Potential of Rainwater Harvesting as an Alternative Source of Clean Water at the Faculty of Science and Technology UIN Walisongo Semarang - Hariz, Anif Rizqianti; Auliana, Indah Nabila (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
Rainwater harvesting (RWH) is the process of directly preventing rainwater runoff and introducing rainwater into a reservoir for daily use. RWH can also be an alternative for providing clean water in the UIN Walisongo campus area. With the construction of new buildings and the addition of the number of students each year, the need for clean water is also increasing. This study aims to determine the quality of rainwater in the FST Building and to analyse the potential of rainwater harvesting as an alternative source of clean water in the FST Building of UIN Walisongo Semarang. This study examined rainwater quality as a clean water alternative in the Faculty of Science and Technology building. The location for taking rainwater samples was carried out at the FST Campus 3 Building. Laboratory tests for rainwater quality were carried out at the Centre for Standardisation and Industrial Pollution Prevention Services (BBSPJPPI) in Semarang. The rainwater samples analyzed met the clean water quality standards based on Ministry of Health Regulation No. 32 of 2017 concerning Environmental Health Quality Standards and Water Health Requirements for Sanitary Hygiene, Swimming Pools, Solus Per Aqua, and Public Baths, except for the organic matter parameter (KMnO4), according to laboratory tests.